Next generation material interfaces for neural engineering. (December 2021) - Wunderlich, Hannah; Kozielski, Kristen L
Graphical abstract: Abstract : Neural implant technology is rapidly progressing, and gaining broad interest in research fields such as electrical engineering, materials science, neurobiology, and data science. As the potential applications of neural devices have increased, new technologies to make neural intervention longer-lasting and less invasive have brought attention to neural interface engineering. This review will focus on recent developments in materials for neural implants, highlighting new technologies in the fields of soft electrodes, mechanical and chemical engineering of interface coatings, and remotely powered devices. In this context, novel implantation strategies, manufacturing methods, and combinatorial device functions will also be discussed.